1995
DOI: 10.1111/j.1751-0813.1995.tb15033.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation ofPasteurella multocidaisolated from fowl cholera outbreaks on turkey farms

Abstract: Biochemical profiles, restriction endonuclease analysis (REA) and ribotyping were used to investigate Pasteurella multocida isolates from outbreaks of fowl cholera on 7 turkey farms in New South Wales. While only a single isolate was available from 5 of the farms, multiple isolates, 4 and 12 respectively, were available from the other 2 farms. The available field evidence suggested that 8 outbreaks had occurred with one farm suffering 2 outbreaks. The isolates obtained were all confirmed as Pasteurella multoci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
48
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 15 publications
4
48
0
1
Order By: Relevance
“…Previous work from our group had indicated that outbreaks of fowl cholera in both turkeys and free-range layers were associated with single clones of P. multocida (Blackall et al, 1995, Zhang et al, 2004. Indeed, in the free-range layer outbreak, two outbreaks separated by 10 years were associated with the same strain (Zhang et al, 2004).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Previous work from our group had indicated that outbreaks of fowl cholera in both turkeys and free-range layers were associated with single clones of P. multocida (Blackall et al, 1995, Zhang et al, 2004. Indeed, in the free-range layer outbreak, two outbreaks separated by 10 years were associated with the same strain (Zhang et al, 2004).…”
Section: Discussionmentioning
confidence: 89%
“…There have been many studies on the epidemiology of fowl cholera outbreaks in a variety of hosts; for example, in turkeys (Snipes et al, 1989(Snipes et al, , 1990Christiansen et al, 1992;Blackall et al, 1995;Kardos & Kiss, 2005), geese (Kardos & Kiss, 2005), free-range layers (Zhang et al, 2004), conventional layer flocks (Shivachandra et al, 2005;Eigaard et al, 2006), backyard poultry (Christensen et al, 1998) and ducks (Muhairwa et al, 2000). Unlike these prior studies, our current study has used both a phenotypic method (Heddleston serotyping) as well as a genotypic method (MLST).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The molecular-based techniques of restriction endonuclease analysis and ribotyping have been used extensively to demonstrate considerable diversity in avian isolates of P. multocida (Kim & Nagaraja, 1990;Carpenter et al, 1991;Christiansen et al, 1992a, b;Wilson et al, 1993Wilson et al, , 1995Blackall et al, 1995). While this evidence of diversity is well known, there has been no attempt to assemble an overview of the overall population structure of avian P. multocida isolates in relation to this diversity.…”
Section: Introductionmentioning
confidence: 99%
“…Previous epidemiological investigations have demonstrated that P. multocida associated with fowl cholera in single domestic turkey flocks may belong to multiple clones (Snipes et al ., 1989(Snipes et al ., , 1990Christiansen et al ., 1992;Rhoades et al ., 1992), indicating the importance of characterizing multiple isolates from fowl cholera outbreaks to obtain reliable epidemiological information. The association of a single clone with outbreaks of fowl cholera has been reported in turkey (Christiansen et al ., 1992;Blackall et al ., 1995) and layer flocks (Zhang et al ., 2004), but this was based on relatively few isolates. A different clone of P. multocida was found in each of four outbreaks of fowl cholera on a duck farm over a 2-year period (Muhairwa et al ., 2000).…”
Section: Introductionmentioning
confidence: 99%